Investigation of hydrogen diffusion behavior in 12Cr2Mo1R(H) steel by electrochemical tests and first-principles calculation. Issue 1 (20th December 2021) - Qiu, Xiang; Zhang, Kun; Kang, Qin; Fan, Yicheng; San, Hongyu; Chen, Yiqing; Zhao, Heming
Abstract : Purpose: This paper aims to study the mechanism of hydrogen embrittlement in 12Cr2Mo1R(H) steel, which will help to provide valuable information for the subsequent hydrogen embrittlement research of this kind of steel, so as to optimize the processing technology and take more appropriate measures to prevent hydrogen damage. Design/methodology/approach: The hydrogen diffusion coefficient of 12Cr2Mo1R(H) steel was measured by the hydrogen permeation technique of double electrolytic cells. Moreover, the influence of hydrogen traps in the material and experimental temperature on hydrogen diffusion behavior was discussed. The first-principles calculations based on density functional theory were used to study the occupancy of H atoms in the bcc-Fe cell, the diffusion path and the interaction with vacancy defects. Findings: The results revealed that the logarithm of the hydrogen diffusion coefficient of the material has a linear relationship with the reciprocal of temperature and the activation energy of hydrogen atom diffusion in 12Cr2Mo1R(H) steel is 23.47 kJ/mol. H atoms stably exist in the nearly octahedral interstices in the crystal cell with vacancies. In addition, the solution of Cr/Mo alloy atom does not change the lowest energy path of H atom, but increases the diffusion activation energy of hydrogen atom, thus hindering the diffusion of hydrogen atom. Cr/Mo and vacancy have a synergistic effect on inhibiting the diffusion of H atoms in α-Fe. Originality/value: This article combines experiments with first-principles calculations to explore the diffusion behavior of hydrogen in 12Cr2Mo1R(H) steel from the macroscopic and microscopic perspectives, which will help to establish a calculation model with complex defects in the future.